Motility-mediated regulation of virulence in Pseudomonas syringae. (July 2016) - Ichinose, Yuki; Sawada, Takahiro; Matsui, Hidenori; Yamamoto, Mikihiro; Toyoda, Kazuhiro; Noutoshi, Yoshiteru; Taguchi, Fumiko
Abstract: We have investigated Pseudomonas syringae pv. tabaci –plant interactions using a large variety of virulence-related mutants. A flagellin-defective mutant, Δ fliC, lost flagellar motility and the ability to produce N -acyl homoserine lactones; it had reduced ability to cause disease symptoms, but the expression of genes encoding a multidrug efflux pump transporter, mexEFoprN, was activated. A type IV pili (T4P)-defective mutant, Δ pilA, lost swarming motility, had reduced expression of hrp -related genes and virulence toward the host tobacco plant, but expression of the genes encoding another multidrug efflux pump transporter, mexABoprM, was activated. These results suggest that the genes regulating flagella- and T4P-mediated motilities also regulate expression of other virulence-related genes. Highlights: Gene expression of motility defective mutants in Pseudomonas syringae pv. tabaci was investigated. Flagella-defective mutants lost quorum sensing system. Type IV pili (T4P)-defective mutant lost swarming motility. Motility-defective mutants activate genes for multidrug efflux pump transporter. Genes regulating flagella- and T4P-mediated motilities also regulate expression of other virulence-related genes.